2016
DOI: 10.1186/s13756-016-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of proportion estimates of Extended-Spectrum-Beta-Lactamase-producing Enterobacteriaceae in East Africa hospitals

Abstract: BackgroundA high proportion of Extended-Spectrum-Beta-Lactamase (ESBL) producing Enterobacteriaceae is causing common infections in all regions of the world. The burden of antibiotic resistance due to ESBL in East Africa is large but information is scarce and thus it is unclear how big the problem really is. To gain insight into the magnitude and molecular epidemiology of ESBL-producing Enterobacteriaceae in East Africa a literature search was performed in PubMed on 31 July 2015 to retrieve articles with relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
65
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 62 publications
(70 reference statements)
19
65
5
Order By: Relevance
“…In this review E. coli and K. pneumoniae were predominant ESBL‐PE; an observation previously reported within and outside the African continent (Lautenbach, Patel, Bilker, Edelstein, & Fishman, ; Sonda et al., ; Storberg, ). The worldwide pandemic clone E. coli ST131 (Nicolas‐Chanoine et al., , ) predominated in this review (Moremi et al., ; Mshana et al., ; Mshana, Imirzalioglu, et al., ; Seni et al., ).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In this review E. coli and K. pneumoniae were predominant ESBL‐PE; an observation previously reported within and outside the African continent (Lautenbach, Patel, Bilker, Edelstein, & Fishman, ; Sonda et al., ; Storberg, ). The worldwide pandemic clone E. coli ST131 (Nicolas‐Chanoine et al., , ) predominated in this review (Moremi et al., ; Mshana et al., ; Mshana, Imirzalioglu, et al., ; Seni et al., ).…”
Section: Discussionsupporting
confidence: 58%
“…In this review, the overall ESBL‐PE prevalence pooled from the three interfaces was found to be 22.6%, which is within the range of ESBL prevalence in other African countries such as Kenya, Algeria and Cameroon irrespective of the categories (Kiiru, Kariuki, Goddeeris, & Butaye, ; Storberg, ). However, this overall prevalence is lower compared to 42% reported among humans in East African hospitals (Sonda et al., ). Prevalence in the later may be accounted by the fact that these ESBL bacterial isolates were from patients in the hospitals where MDR bacteria prevail.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…On the other hand, carbapenemases are carbapenem-hydrolyzing beta-lactamases that confer resistance to a broad spectrum of beta-lactam substrates, including carbapenems. Recent studies performed in the region of East Africa show a wide variation in ESBLs prevalence in hospitals between the different countries with a pooled proportion of 40% reported in a meta-analysis (23). Carbapenemases have been documented in several countries in Africa and Rendani et al in their systematic review have suggested that the problem might be bigger than what is currently estimated due to underreporting (11).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies in East Africa have also documented high rates of ESBL-PE from clinical settings (8,9).…”
Section: Introductionmentioning
confidence: 99%